2018
DOI: 10.1002/mds3.10020
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of commercially available compression feedback devices in novice and experienced healthcare practitioners: A prospective randomized simulation study

Abstract: Background Guidelines note the importance of chest compression components including rate, depth, no‐flow time and chest recoil. Audio‐visual feedback (AVF) technologies are included in the American Heart Association's training videos and loosely recommended by the 2015 guidelines. Objective To compare the effectiveness of 3 compression AVF devices compared to standard compressions. Methods Prospective simulation study of 118 subjects randomized into 4 groups: TrueCPR™, Pocket CPR™, CPR RsQ Assist® and Control.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(59 reference statements)
0
5
0
Order By: Relevance
“… 7 , 8 Several clinical and simulation studies have reported improved quality of compression components using AVF devices. 9 , 10 , 11 , 12 , 13 , 14 , 15 Furthermore, both the American Heart Association and the International Liaison Committee on Resuscitation have issued cautious recommendations to support the use of AVF equipment. 16 , 17 , 18…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 7 , 8 Several clinical and simulation studies have reported improved quality of compression components using AVF devices. 9 , 10 , 11 , 12 , 13 , 14 , 15 Furthermore, both the American Heart Association and the International Liaison Committee on Resuscitation have issued cautious recommendations to support the use of AVF equipment. 16 , 17 , 18…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Several clinical and simulation studies have reported improved quality of compression components using AVF devices. [9][10][11][12][13][14][15] Furthermore, both the American Heart Association and the International Liaison Committee on Resuscitation have issued cautious recommendations to support the use of AVF equipment. [16][17][18] The AVF devices can be categorized as devices related or unrelated to automated external defibrillators (AEDs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliant technology ranges in complexity from a metronome to tensile springs, accelerometers, pressure sensors, and triaxial magnetic sensing [ Table 1 ]. [ 3 42 43 44 45 46 47 48 49 50 51 ] Feedback may be given in audio, visual, or tactile format. Stand-alone AVF devices provide benefits in cost and simplicity, making them potentially useful for applications both in-and outside of hospital settings.…”
Section: Introductionmentioning
confidence: 99%
“…Data comparing free-standing non-AED AVF devices head-to-head are far fewer,[ 42 50 68 69 70 71 72 ] and which devices display the highest performance remains unclear. The objective of this project is to address the following research question: in patients with IHCA (population), does chest compression performed with a free-standing non-AED AVF device as compared to standard manual chest compressions (comparison) result in improved outcomes including sustained ROSC, and survival to ICU and survival to hospital discharge (outcomes).…”
Section: Introductionmentioning
confidence: 99%